Testosterone supplementation in men: a practical guide for the gynecologist and obstetrician. Issue 4 (August 2015) - Owen, Ryan C.; Elkelany, Osama O.; Kim, Edward D.
Abstract : Purpose of review: Prescribing habits for the treatment of symptomatic hypogonadism have recently stirred controversy surrounding testosterone replacement therapy. As a result, the gynecologist will need to recognize this iatrogenic form of decreased sperm production in couples seeking fertility advice. We have compiled a review of the current literature on testosterone supplementation pertaining to the gynecologic practice. Recent findings: Over the last decade, testosterone use has seen a recent increase including in men desiring to become fathers. Many physicians and hypogonadal men do not recognize that testosterone replacement therapy can have a detrimental effect on spermatogenesis. Fortunately, the cessation of treatment will yield predictable recovery of sperm production for most men. A growing body of evidence supports the use of selective estrogen receptor modulators, such as clomiphene citrate, or human chorionic gonadotropin for the treatment of hypogonadism in men who wish to maintain fertility potential. Recently, the Food and Drug Administration has recommended a labeling update on testosterone products to warn of possible increased risk of venous thromboembolism, cardiovascular events and stroke. Summary: Clinicians should be familiar with current practices involving testosterone replacement therapy and the implications on male factor fertility.